The Strengthening of Integrity Character through Exemplary Practices in Islamic Religious Education - Romi Romi; Muhammad Sabli; Sugeng Kurniawan; Sriani Sriani; Ulfa Adilla; Sonia Yulia Friska (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
The decline of moral integrity among students has become a strategic challenge in the national education system, particularly at the junior secondary Islamic school level, where adolescents are undergoing a critical stage of moral identity development. This study aims to analyze the implementation, impacts, and supporting and inhibiting factors of strengthening integrity character through exemplary-based Islamic Religious Education (IRE) at MTs Tarbiyah Islamiyah Tanjung Agung, Bungo Regency. The study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and document analysis involving Islamic Religious Education teachers, students, the school principal, and parents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while source and method triangulation were applied to ensure data trustworthiness. The findings reveal that: (1) the implementation of exemplary practices in Islamic Religious Education was reflected in teachers’ behavioral consistency, transparent assessment practices, ethical communication, and the integration of integrity values into co-curricular activities; (2) exemplary-based learning significantly strengthened the cognitive, affective, and behavioral dimensions of students’ integrity, as evidenced by a reduction in cheating practices, increased honesty in completing assignments, and greater courage in making consistent moral decisions; and (3) supporting factors included a religious school culture, parental involvement, and teacher commitment, while inhibiting factors comprised digital distractions, peer pressure, limited character assessment instruments, and teachers’ administrative workload. These findings confirm the relevance of exemplary role-modeling theory in Islamic pedagogy and Social Cognitive Theory within the context of contemporary Islamic secondary education. The study recommends the development of operational guidelines for exemplary practices among Islamic Religious Education teachers, the integration of character assessment into school evaluation systems, and the provision of continuous reflective professional development for educators.